THE STUDY OF THE HUMAN RESOURCES AND GOOD GOVERNANCE. - RiaLutviDiarini, Novi Puspitasari, Sri Wahyu Lelly Hana Setiyanti (International Journal of Research Science and Management, 2018)
This study aims to discuss the human resource crisis, namely efforts to overcome the decrease in the number of officers, decreasing competence, improving the performance of operational officers and maintenance of irrigation networks, organizational governance, and irrigation services to the community. The object of this research is UPTD Irrigation Department and Spatial Planning Probolinggo District. The research method used is qualitative design with case study approach. The result of the research shows the efforts can be done in facing the human resource crisis by holding recruitment of freelance, increasing cooperation and communication with P3A / GP3A, maximizing the performance of officers by means of duplicate system, and conducting training / technical guidance irrigation. Organizational governance in UPTD Irrigation Probolinggo PUPR Office can be said a quite good company even with all the limitations. This is evidenced by the presence of 7 UPTD Irrigation in Probolinggo District and the establishment of Irrigation Commission of Probolinggo District. Irrigation services run in accordance with the principles of good organizational governance, namely the existence of transparency, justice in water distribution, participation and responsiveness. However, there has been no accountability report on the performance of PPA and UPTD every month to PUPRProbolinggo District.